Proximate Composition, Total Phenolic Content, and Sensory Analysis of Rice Bran Tempeh - Cempaka, Laras; Eliza, Naila; Ardiansyah, Ardiansyah; Handoko, Dody D.; Astuti, Rizki Maryam (Makara Journal of Science, 2018)
Tempeh is a fermented food prepared using the rawmaterials of soybean fermented by Rhizopus sp. This traditional food is fairly highly consumed in Indonesia. Soybean, which is the primary raw material used in the processing of tempeh, is still being imported due to its insufficient production in Indonesia. Rice bran can be used as a substitute forsoybeans in tempeh processing to add to its (health) benefit. Rice bran has good nutritional value as it contains a high total content of phenolic compounds, dietary fiber, fat, and the amino acid lysine. Thus, rice bran provides anopportunity to use it as a product with functional properties. This study was conducted to determine the proximate characteristics, the total phenolic content (TPC), and the sensory properties of tempeh with the addition of rice bran, chitosan, andgluconodelta-lactone (GDL). The addition of chitosan was used as a source of prebiotic, and GDL was required to accelerate the fermentation process. The chemical characteristics (protein, fat, and water content), the TPC, and the sensory properties (color, aroma, texture, and overall acceptability) of rice bran tempeh were analyzed. Results showed that the tempeh sample with the addition of 20% (w/w) rice bran showed the best sensory analysis. It consisted of 57.23% of water content, 37.42% of protein content, 19.72% of fat content, and 83.98 mg GAE/100 g of TPC.